Male or Female? Brains are Intersex - Joel, Daphna (Frontiers in Integrative Neuroscience, 2011)
The underlying assumption in popular and scientific publications on sex differences in the brain is that human brains can take one of two forms “male” or “female”, and that the differences between these two forms underlie differences between men and women in personality, cognition, emotion and behavior. Documented sex differences in brain structure are typically taken to support this dimorphic view of the brain. However, neuroanatomical data reveal that sex interacts with other factors in utero and throughout life to determine the structure of the brain, and that because these interactions are complex, the result is a multi-morphic, rather than a dimorphic, brain. More specifically, here I argue that human brains are composed of an ever-changing heterogeneous mosaic of “male” and “female” brain characteristics (rather than being all “male” or all “female”) that cannot be aligned on a continuum between a “male brain” and a “female brain”. I further suggest that sex differences in the direction of change in the brain mosaic following specific environmental events lead to sex differences in neuropsychiatric disorders.